2021
DOI: 10.1111/1462-2920.15855
|View full text |Cite
|
Sign up to set email alerts
|

Widespread contamination of SARS‐CoV‐2 on highly touched surfaces in Brazil during the second wave of the COVID‐19 pandemic

Abstract: Although SARS-CoV-2 surface contamination has been investigated in health care settings, little is known about the SARS-CoV-2 surface contamination in public urban areas, particularly in tropical countries. Here, we investigated the presence of SARS-CoV-2 on high-touch surfaces in a large city in Brazil, one of the most affected countries by the COVID-19 pandemic in the world. A total of 400 surface samples were collected in February 2021 in the City of Recife, Northeastern Brazil. A total of 97 samples (24.2%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Importantly, the majority of these studies did not investigate the capacity of SARS-CoV-2 to be cultured from an environmental surface sample, which is crucial for understanding the role of SARS-CoV-2 RNA-positive samples in terms of infectious potential toward the human population. 130 , 132 , 136 Taken together, recent aggregated studies reinforce the potential of environmental samples for SARS-CoV-2 transmission ( i.e. , indirect contact), although virus spread via close contact remains the primary route for SARS-CoV-2 transmission.…”
Section: Modes Of Transmissionmentioning
confidence: 71%
See 1 more Smart Citation
“…Importantly, the majority of these studies did not investigate the capacity of SARS-CoV-2 to be cultured from an environmental surface sample, which is crucial for understanding the role of SARS-CoV-2 RNA-positive samples in terms of infectious potential toward the human population. 130 , 132 , 136 Taken together, recent aggregated studies reinforce the potential of environmental samples for SARS-CoV-2 transmission ( i.e. , indirect contact), although virus spread via close contact remains the primary route for SARS-CoV-2 transmission.…”
Section: Modes Of Transmissionmentioning
confidence: 71%
“… 126 , 133 135 The results demonstrate different levels of viral contamination varying from high 130 , 136 to low 132 or even no contamination by SARS-CoV-2 RNA. 134 Additionally, most of the reported positive environmental samples were found to have high reverse transcription quantitative polymerase chain reaction (RT-qPCR) cycle threshold (Ct) values (>30) for most of the positive samples, 130 , 136 indicating low viral load and the labile nature of SARS-CoV-2 in the environment. Importantly, the majority of these studies did not investigate the capacity of SARS-CoV-2 to be cultured from an environmental surface sample, which is crucial for understanding the role of SARS-CoV-2 RNA-positive samples in terms of infectious potential toward the human population.…”
Section: Modes Of Transmissionmentioning
confidence: 91%
“…Traveling by public transport is considered dangerous as SARS-CoV-2 is a highly contagious pathogen, with many asymptomatic individuals [ 46 ]. A study in Brazil confirmed that people who use public transport are more exposed to contracting the coronavirus [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 studies (48%) pre-specified the Ct for positive tests ( Table 1 ); studies using commercially available RT-PCR assays used the manufacturer specified Ct threshold as indicated in the product insert for the assay. Four studies [ 20 , 21 , 23 , 25 ] used a cut-off of <40, and two studies [ 12 , 24 ] used <35. Four studies used the following cut-offs: <45 [ 32 ], <40·4 [ 33 ], <39 [ 13 ], and <38 [ 30 ].…”
Section: Resultsmentioning
confidence: 99%